2009
DOI: 10.1007/s13312-010-0064-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum ALT: LDH ratio in typhoid fever and acute viral hepatitis

Abstract: In 100 consecutive children aged below 18 years with confirmed typhoid fever, 29 had moderate hepatitis. Serum alanine amino transferase: lactate dehydrogenase (ALT: LDH) ratios of these 29 children at the time of hospitalization were compared with that of 29 children with acute viral hepatitis. The serum ALT: LDH ratio levels (expressed in multiples of upper limit of normal) was found to be less than 9 in typhoid hepatitis and more than 9 in acute viral hepatitis. Serum ALT: LDH ratio helps to differentiate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…The elevated serum LDH levels have been reported to be the diagnostic markers of various illnesses in humans, including the life-threatening bacterial infection 10 . The report on LDH isoforms analysis has, however, been scanty 6 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The elevated serum LDH levels have been reported to be the diagnostic markers of various illnesses in humans, including the life-threatening bacterial infection 10 . The report on LDH isoforms analysis has, however, been scanty 6 .…”
Section: Resultsmentioning
confidence: 99%
“…The LDH has been studied as a diagnostic marker of noninfectious 7-9 as well as infectious diseases, including bacterial infection 6,10 . The infection with bacterial pathogens including group A streptococci causes a number of diseases, in humans, with multiple organs involvement and tissue damages leading to the secretion of LDH releasing into the blood 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The elevated serum LDH levels have been reported to be the diagnostic markers of various illnesses in humans, including the life-threatening bacterial infection [32]. This study demonstrated the serum LDH profiles in dengue cases as well as non-dengue subjects, first time, within and around Malda, India, in order to confirm the intensity of LDH bands in the stained gel ( Figure 4), from PAGE system, with the estimated levels of serum LDH in cases as well as non-dengue individuals.…”
Section: Resultsmentioning
confidence: 99%
“…[2,6] In children, serum aminotransferase levels are markedly elevated in viral hepatitis (8-10 times normal) as compared to typhoid hepatitis, and the ratio of AST/LDH is more than 9 in viral hepatitis. [2,7,8] Balasubramanian et al found that, on admission, children with typhoid hepatitis had ALT: LDH values below 9, and those with an acute viral hepatitis had the values above 9. [7] Other differentiating clinical features in typhoid fever include high grade fever, toxic appearance, relative bradycardia, relative lymphocytosis with leucopenia and an absence of deep jaundice.…”
Section: Discussionmentioning
confidence: 99%
“…[2,7,8] Balasubramanian et al found that, on admission, children with typhoid hepatitis had ALT: LDH values below 9, and those with an acute viral hepatitis had the values above 9. [7] Other differentiating clinical features in typhoid fever include high grade fever, toxic appearance, relative bradycardia, relative lymphocytosis with leucopenia and an absence of deep jaundice. [6] The coagulation profile is usually normal in typhoid fever even in the presence of elevated hepatic enzymes.…”
Section: Discussionmentioning
confidence: 99%